SPE Production and Operations Symposium 2011
DOI: 10.2118/141458-ms
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Casing Design with Finite-Element Model of Effective Dogleg Severity, Radial Displacements and Bending Loads

Abstract: A purpose-built finite-element model (FEM) is applied to simulate radial displacement of a casing string constrained within an outer wellbore. The FEM represents a fully stiff-string model wherein the casing is approximated by general beam elements with 6 degrees of freedom at each node to account for all possible physical displacements and rotations. Results predicted include deflection of the casing centerline from the wellbore centerline, effective dogleg curvature, bending deformation, wall contact forces,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, it is only in recent years that the research on the mechanics of the perforated tube string has been carried out [4][5][6][7][8][9][10][11]. Using the gap element theory of finite element method (FEM), a three-dimensional static analysis model of a perforated tube string was established by Zhang et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is only in recent years that the research on the mechanics of the perforated tube string has been carried out [4][5][6][7][8][9][10][11]. Using the gap element theory of finite element method (FEM), a three-dimensional static analysis model of a perforated tube string was established by Zhang et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…Stefan Miska et al [12] take the effect of wellbore torsion into consideration, and developed a three-dimensional model to calculate the axial force and the contact force along the casing. McSpadden et al [13] discussed the axial force, shear moment and stress along the length of the casing string with stiff string model, and demonstrated that optimized casing-design efficiency may be achieved by avoiding overly conservative and costly design for HP/HT and extreme-temperature wells.…”
Section: Introductionmentioning
confidence: 99%
“…A purpose-built fi nite-element model is applied by Mc-Spadden, Coker, et al [1] to simulate radial displace ment of a casing string constrained within an outer well bore. This represents a fully stiff -string model wherein the casing is approximated by general beam elements with 6 degrees of freedom at each node to account for all possible physical displacements and rotations.…”
mentioning
confidence: 99%